1990
DOI: 10.1002/nau.1930090505
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle exercise for the treatment of female stress urinary incontinence: III. Effects of two different degrees of pelvic floor muscle exercises

Abstract: Fifty-two women. mean age 45.9 years (24-64) with clinically and urodynamically proven stress urinary incontinence (SUI) were randomly assigned to one of two different pelvic floor muscle (PFM) exercise groups. Both groups performed 8-12 maximal PFM contractions 3 times a day for 6 months. In addition one group exercised with an instructor intensively 45 min once a week performing long-lasting contractions with the supplement of 3-4 fast contractions at the end of each long-lasting contraction.Initially and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
138
2
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 312 publications
(156 citation statements)
references
References 15 publications
4
138
2
6
Order By: Relevance
“…Cure and improvement rates were consistently higher for women who received additional supervisory sessions ( Figures 12 and 13: cure rate, 15% vs 43%, OR 0.11, 95% CI 0.03 to 0.43; One small study 159 with 15 years of follow-up also reported that the number of women who remained continent (cured) after they were left to continue PFMT on their own was higher in the group who had additional sessions during the initial supervised treatment phase, although this difference was not statistically significant (Appendix 17, Comparison 03, 16% vs 30%, OR 0.44, 95% CI 0.11 to 1.87).…”
Section: Cure and Improvement Ratementioning
confidence: 98%
See 4 more Smart Citations
“…Cure and improvement rates were consistently higher for women who received additional supervisory sessions ( Figures 12 and 13: cure rate, 15% vs 43%, OR 0.11, 95% CI 0.03 to 0.43; One small study 159 with 15 years of follow-up also reported that the number of women who remained continent (cured) after they were left to continue PFMT on their own was higher in the group who had additional sessions during the initial supervised treatment phase, although this difference was not statistically significant (Appendix 17, Comparison 03, 16% vs 30%, OR 0.44, 95% CI 0.11 to 1.87).…”
Section: Cure and Improvement Ratementioning
confidence: 98%
“…Two studies 116,159 provided data amenable to quantitative synthesis; results showed a statistically significant difference between the groups favouring PFMT with additional sessions (Appendix 19, Comparison 02, SMD -1.07, 95% CI -1.98 to -0.15).…”
Section: Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations